Meningkatkan Perkembangan Motorik Halus Anak dengan Kegiatan Menulis pada Usia 5-6 Tahun di Tk Negeri Pembina Gorontalo - Sri Muliyana Taha; Siti Endang; Siti Magfira Biludi; Siti Fadilah Tahir; Annisa Fahmi Mannassai; Sri Yulan Umar (Institut Nalanda, 2025)
The purpose of this study was to determine The Improvement of Fine Motor Development of Children Aged 5-6 Years Through WritingActivitiesat TK Negeri Gorontalo Thisresearchis Classroom Action Research (CAR) whichconsists of II Cycles starting with the stages of Planning, Implementation, Observation and Reflection. Data collectiontechniques are Observation, Documentation and Assessmentinstrumentsheet. The subjects in this study were 10 childrenaged 5 -6 yearsat TK Negeri Gorontalo. The study results showed that writing activities improve children's fine motor developmentat Tk Negeri Gorontalo. Itwasproven by the data In firstcycleitwasfoundthat 1 child (10%) with the criteria of Very Good Development (BSB), 5children (50%) with the criteria of Developing as Expected (BSH), 3 children (30%) with the criteria of Starting to Develop (MB) and 1 children (10%) with criteria not yetdeveloped (BB). While in the secondcycletherewasanincrease, namely 8 children (80%) with verygooddevelopmentcriteria (BSB) and 2 children (20%) developingaccording to expectations (BSH). In the secondcycle, itwasfoundthat the results of this study had reached the indicator of success of 80% with anassessmentcategory were 76% of the number of children. So it can be concluded that writing activities in Pembina State Kindergarten can improve the fine motor development of children aged 5 - 6 years. Keywords :